2020
DOI: 10.1186/s12875-020-01337-0
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, governance and management for improving district capacity and performance: the case of USAID transform: primary health care

Abstract: Background Primary health care (PHC) in Ethiopia serves as the main entry point for preventive, promotive and curative health services. The district health office is responsible for the planning, implementation and evaluation of all district health activities. In addition, district health offices manage service delivery facilities working on provision of PHC – primary hospitals, health centers and health posts. As the leader of the health care system tier, district health management must ensure direction, alig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…Hence, the multi-faceted LMG intervention addresses some gaps in desired competencies and skills of health workers which enables them to solve existing challenges in their workplace. These findings were consistent with other similar studies documented that show significant increases of health service coverage as a result of LMG training and interventions in Zambia, Gambia, Egypt, Ethiopia, Ghana, Kenya and Mozambique [ 3 , 6 , 11 15 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, the multi-faceted LMG intervention addresses some gaps in desired competencies and skills of health workers which enables them to solve existing challenges in their workplace. These findings were consistent with other similar studies documented that show significant increases of health service coverage as a result of LMG training and interventions in Zambia, Gambia, Egypt, Ethiopia, Ghana, Kenya and Mozambique [ 3 , 6 , 11 15 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…This gain might be a result of the capacity building interventions in leading, managing, and governing practices. This finding is consistent with the Desta et al [ 37 ] comparative reports of LMG intervention districts which were better at capacitating health workers, strengthening teams, and availing inputs than non-LMG intervention districts. Similarly, La Rue et al [ 11 ], confirm that health service coverages were better in intervention districts than non-intervention districts through strengthening of leadership and management skills.…”
Section: Discussionsupporting
confidence: 91%
“…Leadership training and mentoring sessions, facilitated with the support of partners build the leadership capacity and competencies of women, and prepare them to be competent for leadership dispensation. This finding aligns with that of Desta et al (2020) and Argaw et al (2021), where facilitating leadership training and coaching activities were found to be effective in building the desired competencies [ 38 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…Additional efforts through documentation, sharing vision or mission among all staff, enhanced organizing and aligning resource capacities, motivation of staff, also contribute to positive results. Desta et al, (2020) documented that LMG intervention districts were better at capacitating health workers, strengthening teams, and availing inputs than non-LMG intervention districts [37]. Similarly, La Rue et al, (2012), con rm that health service coverages were better in intervention districts than comparison districts through strengthening of leadership and management skills [11].…”
Section: Discussionmentioning
confidence: 99%